2012
DOI: 10.1021/cg3007734
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneity of Nacre Lamellae on the Nanometer Length Scale

Abstract: We present experimental evidence of inhomogeneous distribution of organic inclusions within individual aragonitic lamellae forming the nacre layer of mollusk shells. This nanoscale-inhomogeneity is visualized in the Perna canaliculus (green mussel) shells by the aid of high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) in the tomography mode. Electron tomography reconstructions of the three-dimensional distribution of intracrystalline organic inclusions, ranging in size betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 61 publications
10
79
2
Order By: Relevance
“…Gilow et al [12] also concluded that organic molecules attach preferentially to the highly charged f001g planes of the prismatic calcite of Pinna (which is a close relative of Atrina). A similar pattern has been recently observed in the nacre of the mussel Perna [33]. Organic molecules occluded within the crystals and distributed around the boundaries of 200-300 nm crystalline domains (similar to the ones which we report here; figure 6a-c,e-i) were imaged with TEM in the calcites of the pterioidean Pinctada and in the ostreoidean Crassostrea [13,34]; the boundaries are characterized by small misorientations, in coincidence with small distortions of the crystal lattice.…”
Section: Discussionsupporting
confidence: 85%
“…Gilow et al [12] also concluded that organic molecules attach preferentially to the highly charged f001g planes of the prismatic calcite of Pinna (which is a close relative of Atrina). A similar pattern has been recently observed in the nacre of the mussel Perna [33]. Organic molecules occluded within the crystals and distributed around the boundaries of 200-300 nm crystalline domains (similar to the ones which we report here; figure 6a-c,e-i) were imaged with TEM in the calcites of the pterioidean Pinctada and in the ostreoidean Crassostrea [13,34]; the boundaries are characterized by small misorientations, in coincidence with small distortions of the crystal lattice.…”
Section: Discussionsupporting
confidence: 85%
“…For each stage, we developed analytical or semi-analytical approximations to the distribution of elongation U , strength L, and the toughness modulus T . Qualitatively, our results are in agreement with previous work on fracture in materials with randomly disordered Young's modulus distributions (Dimas et al, 2014;Tai et al, 2007;Younis et al, 2012). The methods depend to some extent on the Euclidean dimension of the specimen (n 1 = or 2), the quantity considered (U, L, or T ), and the condition under which the probability distribution is assessed (fracture initiation I or ultimate failure U ).…”
Section: Discussionsupporting
confidence: 89%
“…Hence the force-displacement plots are consistent with what has been observed in layered materials when fracture propagates towards softer or stiffer layers (Delale and Erdogan, 1983;Fratzl et al, 2007;Romeo and Ballarini, 1995;Zak and Williams, 1963). To verify this interpretation, we considered a bi-material specimen patterned to idealize case (b).…”
Section: Numerical Modelssupporting
confidence: 75%
See 2 more Smart Citations